Activation of Adenosine A3 Receptor Alleviates TNF-α-Induced Inflammation through Inhibition of the NF-κB Signaling Pathway in Human Colonic Epithelial Cells. (22nd April 2014) - Ren, Tianhua; Qiu, Yumei; Wu, Weiyun; Feng, Xiao; Ye, Shicai; Wang, Zhuang; Tian, Ting; He, Yanting; Yu, Caiyuan; Zhou, Yu
Abstract : To investigate the expression of adenosine A3 receptor (A3AR) in human colonic epithelial cells and the effects of A3AR activation on tumor necrosis factor alpha (TNF- α -) induced inflammation in order to determine its mechanism of action in human colonic epithelial cells, human colonic epithelial cells (HT-29 cells) were treated with different concentrations of 2-Cl-IB-MECA prior to TNF- α stimulation, followed by analysis of NF- κ B signaling pathway activation and downstream IL-8 and IL-1 β production. A3AR mRNA and protein were expressed in HT-29 cells and not altered by changes in TNF- α or 2-Cl-IB-MECA. Pretreatment with 2-Cl-IB-MECA prior to stimulation with TNF- α attenuated NF- κ B p65 nuclear translocation as p65 protein decreased in the nucleus of cells and increased in the cytoplasm, inhibited the degradation of I κ B- α, and reduced phosphorylated-I κ B- α level significantly, compared to TNF- α -only-treated groups. Furthermore, 2-Cl-IB-MECA significantly decreased TNF- α -stimulated IL-8 and IL-1 β mRNA expression and secretion, compared to the TNF- α -only treated group. These results confirm that A3AR is expressed in human colonic epithelial cells and demonstrate that its activation has an anti-inflammatory effect, through the inhibition of NF- κ B signaling pathway, which leads to inhibition of downstream IL-8 and IL-1 β expression. Therefore, A3AR activation may be a potential treatment for gut inflammatory diseases such as inflammatory bowel disease.